The Illusion of Leadership: Misattribution of Cause in Coordination Games - Weber, Roberto; Camerer, Colin; Rottenstreich, Yuval; Knez, Marc (Organization Science, 2001)
This paper reports the results of experiments which examine attributions of leadership quality. Subjects played an abstract coordination game which is like many organizational problems. Previous research showed that when larger groups play the game, they rarely coordinate on the Pareto-optimal (efficient) outcome, but small groups almost always coordinate on the efficient outcome. After two or three periods of playing the game, one subject who was randomly selected from among the participants to be the “leader” for the experiment was instructed to make a speech exhorting others to choose the efficient action. Based on previous studies, we predicted that small groups would succeed in achieving efficiency but that large groups would fail. Based on social psychological studies of the fundamental attribution error, we predicted that the subjects would underestimate the strength of the situational effect (group size) and attribute cause to personal traits of the leaders instead—leaders would be credited for the success of the small groups, and blamed for the failure of the large groups. This hypothesis proved true: Subjects attributed differences in outcomes between conditions to differences in the effectiveness of leaders. In a second experiment, subjects voted to replace the leaders more frequently in the large-group condition (at a small cost to themselves), showing that misattributions of leadership ability also affect actual behavior by subjects. Previous research has demonstrated a tendency to credit or blame leaders for unusual performance. The difference in our study is that subjects should be blaming a structural condition—the size of the group—but they blame the leaders instead. Thus, our experiment is the first to establish a mistaken illusion of leadership.